The Effect of Air Pressure and Nozzle Distance on the Quality of Water-Based Painting Using a Gravity-Feed Spray Gun - Mochammad Hildad Ajiban; Heru Arizal; Rachmad Syarifudin Hidayatullah; Firman Yasa Utama (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2024)
Environmental influences can cause corrosion or damage to materials, which is why paint coating is used to protect them. Some of the factors that affect the quality of the paint are technical, such as setting the air pressure and spray gun nozzle spacing. The experimental research aims to determine how air pressures of 1.5, 2, and 2.5 bar and nozzle spacings of 10–15–20 cm affect the gloss and thickness of the water-based paint layer. A gravity-feed spray gun was used for this purpose. The luster test method uses an AMTAST AMN60 glossmeter with the ASTM D523-08 standard, and the thickness test uses a coating thickness gauge with the ASTM E 376-96 standard. The air pressure and the distance of the spray gun nozzle affect the gloss and thickness of the paint layer. Parameter 2 bar/15 cm yielded the highest gloss of 92.77 GU, while parameter 2.5 bar/10 cm resulted in the highest coating thickness of 0.26 mm.